Dihydroisoquinoline copper(ii) complexes: crystal structures, cytotoxicity, and action mechanism. Issue 99 (24th September 2015) - Huang, Ke-Bin; Chen, Zhen-Feng; Liu, Yan-Cheng; Xie, Xiao-Li; Liang, Hong
Abstract : Three new copper(ii ) complexes with dihydroisoquinoline were synthesized. They exhibited considerable cytotoxicity, achieved through the induction of cell apoptosis via the intrinsic pathways of caspase–mitochondria. Abstract : Three new copper(ii ) complexes of 4, 5-methylenedioxy-1-pyridinedihydroisoquinoline (MPDQ), [Cu2 (MPDQ)2 Cl4 ] (1 ), [Cu(MPDQ)(H2 O)(SO4 )] (2 ), and [Cu2 (MPDQ)2 (C2 O4 )(ClO4 )2 ] (3 ) were synthesized and characterized. They exhibit enhanced cytotoxicity against the tested human tumor cells BEL-7404, SK-OV-3, HepG2, A549, A375, MGC-803 and NCI-H460 compared to MPDQ and the corresponding copper(ii ) salts with IC50 values of 1.41–34.54 μM. Complex1 can induce apoptotic death in BEL-7404 by S cell cycle arrest and complex1 -induced apoptosis, which were involved in an intrinsic pathway, including up-regulating P53 and down-regulating Bcl-2 and mitochondrial membrane potential, leading to sequential activation of caspase-9 and caspase-3. ICP-MS testing implied that the copper(ii ) complexes could enter cells and DNA was one important target; DNA binding studies revealed that intercalation might be the most probable binding mode of the new Cu(ii ) complexes with ct-DNA.